Semiotics and its branches (Syntactics, Semantics, Pragmatics) - Shamsutdinova Nazokat Alisherovna (Лучшие интеллектуальные исследования, 2024)
This article is devoted to the study of semiotics, as the science of signs and sign systems, sections of semiotics: Syntactics, Pragmatics, Semantics. Signs and symbols are one of the forms of non-verbal communication that are used universally and widely to convey information. The article talks about the degree of study of semiotics as a science of signs, the branches of semiotics Syntactics, Pragmatics, Semantics and the significance of this branch of scientific knowledge in non-verbal communication. The article gives information about the sign theories of Charles Peirce and Ferdinand de Saussure.